Oblicz wartość liczbową wyrażenia:

a) -y+8x-z-2x dla x= -2 y=6 z= -3

b) -8y-4z+x-y-2z+1 dla x= -0,5 y= -1 z=2

c) 9y-(7y+x)+(6x-7y) dla x= -2 y=3

d) (6a-8b-0,7)-(6,9+a-5b)+1,8 dla a=0,2 b=0,1

e) ½abc-(4ab+2abc)+(-bc+5ab) dla a= -2 b=½ c= -4



Błagam was o pomoc!!!!!!!!

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-03T16:40:29+01:00
A) -y+8x-z-2x= -6+8razy (-2)-(-3)-2razy(-2)= -6+(-16)+3+4=-22+7=-15
b)-8y-4z+x-y-2z+1=-8 razy (-1)-4razy 2+(-0,5)-(-1)-2razy 2+1=8-8-0,5+1-4+1=-2,5
c) 9y-(7y+x)+(6x-7y)=9 razy 3 -(7razy3+(-2))+(6razy(-2)-7razy3)= 27-19+(-12-21)=8+(-33)=8-33=-25
d)(6a-8b-0,7)-(6,9+a-5b)+1,8=(1,2-0,8-0,7)-(6,9+0,2-0,5)=-0,3-6,6=-6,9
e)0,5-(4ab+2abc)+(-bc+5ab)= -2-(-4+8)+(2+(-5))= -2-4-3=-9
1 5 1
2010-02-03T16:40:34+01:00
A.-(-2)+(8*6)-(-3)-2*(-2)
-6+16+3+4= -15

b.-8*(-0.5)-4*2-0.5+1-4+1
4-8-0.5+1-4+1 = -6.5

c(9*3)-(7*3-2)+(-12-21
27-21+2-12-21= -25

d.(1.2-0.8-0.7)-(6.9+0.2-0.5)
1.2-0.8-0.7-6.9-0.2+0.5= -6.9

e½*(-2)*½*(-4) -[4*(-2)*½+2*(-2)*½*(-4)
2-(-4+8)+(2-5)
2+4-8+2-5 = -5
1 5 1
2010-02-03T16:40:49+01:00
A) -y+8x-z-2x dla x= -2 y=6 z= -3

-(-6)+8*(-2)-(-3)-2*(-2)=6-16+3+4=-3


b) -8y-4z+x-y-2z+1 dla x= -0,5 y= -1 z=2

-8*(-1)-4*2+(-0,5)-(-1)-2*2+1=8-8-0,5+1-4=-3,5


c) 9y-(7y+x)+(6x-7y) dla x= -2 y=3

9*3-[7*3+(-2)]+[6*(-2)-7*3]=27-(21-2)+(-12-21)=27-21+2+12+21=41


d) (6a-8b-0,7)-(6,9+a-5b)+1,8 dla a=0,2 b=0,1

(6*0,2-8*0,1-0,7)-(6,9+0,2-5*0,1)=1,2-0,8-0,7-(6,9+0,2-0,5)=
1,2-0,8-0,7-6,9-0,2+0,5=-6,9


e) ½abc-(4ab+2abc)+(-bc+5ab) dla a= -2 b=½ c= -4

1/2 * (-2) * 1/2 * (-4) - [4*(-2)*1/2 + 2*(-2)*1/2*(-4)] + [-1/2*(-4)+5*(-2)*1/2]=2-(-4-8)+(-10)=2+4+8-10=4


Pozdro :)
1 5 1